Health promotion in curriculum and professional nursing training of - Salcedo Zuñiga De Jaime, Maria Clelia (2020)
Objective. To determine the relationship between the approach to Health Promotion applied in curriculum and quality of competitive professional training. Methods. A correlational study was carried out. It comprised of 63 graduates from Professional Academic School of Nurs-ing, Universidad de Huanuco, 2015-2016. A health promotion approach questionnaire applied in the curriculum and a  check format on competitive professional quality were used. Spearman's Rho correlation coefficient was used in the inferential analysis of the results. Results. 74.6 % (47 graduates) had a moderately favorable perception of health promotion ap-proach applied in the curriculum. On the other hand, in the quality of competitive professional training, 58.7 % (37 graduates) showed a poor quality of training. Furthermore, there is a sig-nificant relationship between health promotion approach and quality of competitive profes-sional training (rs = 0.58; p = 0.000), and also between quality of competitive professional training and health promotion approach in primary care (rs = 0.49; p ≤ 0.000), state, society and public policies (rs = 0.49; p ≤ 0.000) and community nursing (rs = 0.39; p ≤ 0.002). Conclusion.There is a positive and significant relationship between the health promotion ap-proach applied in the curriculum plan and the quality of competitive professional training in health promotion.